O reconhecimento judicial da união estável paralela ao casamento: os limites da atuação do estado na regulamentação conjugal - Silva, Ivone Beatriz Cavalcanti da (2021)
The advent of the 1988 constitution provoked a shadow correction in families' law. With a prejudiced interpretation of at least one moral theologian, The constituent, based on a singular understanding, granted the 88's attention to family and friends entities, bringing, to the legal scene, a break in the plastered concept of the family of. It consecrated of dignity to give a Person as the basic human outward guiding, turningprotection prepares to give the individual while outwardly protecting its full capacity to achieve or development. This constitutionalized understanding provides civil guarantee in the shadow of bone models of isonomy among family members, which exists from the will of the subject that each one of his accounts Share in lives through affect. In this sense, Brazilian bone Tribunat would start from feature by a vision based on freedom that no individual conceives his private life, understanding for so long that as constant social changes it impacts a judicial update Oh, mainly frontal as spaces and legislation. Despite two Perceived Advances, many legal hypotheses disregard Oh, as in the case of give unions, constitute in parallel to another stable union or marriage. A factual existence of these relationships wearing consequences that needed the shadow Legal intervention was that it gives a mercer subjectivity to each operator of the Law. We endorse this, from the insecurity that involves the inexistence of a uniform thought oh the Federal Supreme Court on November 21, 2020, for urinating giving electronic bursts 1045273/SE granted General repercussion to Teseo number 529, impossibility of recognizing such simultaneous relationships; invisible had been as vigorously as the dishonest state. In this context the Oh Presence work proposes a conceptual exposition shadow giving the right side of the family as possible disputes out violations perceived in the impossibility of protecting union.